Vitrocerâmica altamente bioativa, de boa resistência mecânica e baixo módulo elástico - Silva, Laís Dantas (2019)
Bioactive glass and glass-ceramics have the property of binding directly to living tissue. However, from mechanical performance, these materials have some disadvantages such as low fracture resistance. Some properties restrict their use in applications that require substantial mechanical effort, like as bone tissue substitutes. In this work, new bioactive glasses compositions of the Na2O-K2O-CaO-SiO2-P2O5 system were prepared with the objective to obtaining glass-ceramics combining high mechanical strength and good bioactivity. For this, a rigorous microstructural control was carried out using thermal treatments. The aim was to achieve acicular crystals, in addition to the development of glass-ceramics through the sintering route. Thermal treatments and microscopy analysis (Optical Microscopy – OM and Scanning Electron Microscopy - SEM) were used together as a microstructural control tools. The crystalline phases formed were identified by X-ray Diffraction. In addition to the confirmation of minority phases through Raman spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). Besides, the hardness was evaluated by the Vickers microhardness technique and the modulus of elasticity using the Impulse Excitation Technique. On the other hand biaxial bending tests were conducted to obtain fracture resistance. In addition, the bioactivity of glasses and glass-ceramics were evaluated by in vitro bioactivity tests using the acellular solution of SBF-K9 (Simulated Body Fluid), followed by FTIR analysis. In which glass-ceramics with acicular morphology with high in vitro bioactivity were obtained. In addition, mechanical strength of ~170 MPa, about three times higher than the original glass, and elastic modulus very close to that of Bioglass 45S5®, reaching a value of approximately 50 GPa. Thus, in this work we obtained a high-performance glass-ceramics with great potential for bone substitution.